2008
DOI: 10.1002/em.20399
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticles trigger p53‐mediated damage response in peripheral blood lymphocytes

Abstract: Titanium dioxide nanoparticles (nano-TiO2) are widely used as a photocatalyst in air and water remediation. These nanoparticles are known to induce toxicity; however, their cytotoxic mechanism is not fully understood. In this study, we investigated the underlying mechanism of nano-TiO2-induced cytotoxicity in peripheral blood lymphocytes. We examined the genotoxic effects of nano-TiO2 in lymphocytes using alkaline single-cell gel electrophoresis (Comet) and cytokinesis-block micronucleus (CBMN) assays. Lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
156
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(181 citation statements)
references
References 46 publications
16
156
1
5
Order By: Relevance
“…Recent studies have reported chromosomal damage induced by nano-TiO 2 in hamster embryo fibroblasts, blood lymphocytes, and in a human B-cell lymphoblastoid cell line using the micronucleus assay (Kang et al, 2008;Rahman et al, 2002;Wang et al, 2007), which was mostly associated with ROS-related DNA injury. Similarly, an in vivo study has shown the induction of DNA breakage in mice cells after exposure to P25-TiO 2 in drinking water (Trouiller et al, 2009).…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedmentioning
confidence: 99%
“…Recent studies have reported chromosomal damage induced by nano-TiO 2 in hamster embryo fibroblasts, blood lymphocytes, and in a human B-cell lymphoblastoid cell line using the micronucleus assay (Kang et al, 2008;Rahman et al, 2002;Wang et al, 2007), which was mostly associated with ROS-related DNA injury. Similarly, an in vivo study has shown the induction of DNA breakage in mice cells after exposure to P25-TiO 2 in drinking water (Trouiller et al, 2009).…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedmentioning
confidence: 99%
“…The selection of a relevant cell type and source generally depends on the expected in vivo target organ and application of the NP 79 . In the vast majority of the studies the cells are exposed to the NP dispersion during a single incubation period ranging from 3 up to 48 hours 78,80,81 .…”
Section: A Routine In Vitro Methodsmentioning
confidence: 99%
“…Any reduction in mitochondrial membrane potential can lead to decreased energy production, which may results cytochrome c release and induce cellular apoptosis via calciumsensitive proteases, or through the activation of caspases and DNA fragmentation enzymes (Calcineurin et al 2001). Several studies in different cell lines showed that TiO 2 NP could cause genotoxicity represented by DNA damage and chromosomal aberrations (Rahman et al 2002;Kang et al 2008;Xu et al 2009;Petković et al 2011). The exposure of peripheral human lymphocytes to TiO 2 NPs can lead to the activation of DNA damage check points and accumulation of tumour suppressor protein p53 (Kang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that red blood cells exposed to TiO 2 -NPs showed abnormal sedimentation, hemagglutination and hemolysis. Studies on animal models and in vitro experiments involving various cell lines have further proved the cytotoxicity of TiO 2 -NPs, including the inflammation of many organs according to their rout of entry, induction of chromatin condensation, nuclear fragmentation, caspase activation, and even apoptosis (Kang et al 2008;Zhu et al 2012). The cytotoxicity of TiO 2-NPs depend on their physical and chemical properties, especialy their size, as the smaller the particles, the more damage they cause (Sohaebuddin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation